Pengaruh Inovasi Teknologi, Struktur Modal dan Struktur Kepemilikan terhadap Pengungkapan Laporan Keberlanjutan - Riska Prastyawan; Christina Dwi Astuti (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to examine the effect of Technology Innovation, Capital Structure, Ownership Structure on Sustainability Report Disclosure. The population in this study are Primary Consumer companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. The data used is secondary data obtained from the company’s financial statements through the website www.idx.co.id or the websites of each company. The study used a purposive sampling methode with several criteria and the results obtained as many as 161 sample data. Data analysis method using descriptive test, classical assumption test and multiple linear regressions test using SPSS Software 26. The results show that Technology Innovation, Capital Structure, Institutional Ownership, have positive effect on Sustainability Report Disclosure. Foreign Ownership and Managerial Ownership doesn’t have effect on Sustainability Report Disclosure.